The Effect of Gamification in Shopee Games on User’s Brand Loyalty - Bulu, Debora Soli; Natalia, El Chris (Mediator: Jurnal Komunikasi, 2024)
Shopee, one of the e-commerce companies, implements gamification through the Shopee Games on the Shopee application. The existence of Shopee Games can provide satisfaction to users, which can lead to the growth of Shopee users’ brand loyalty. Therefore, this research aims to analyze the effect of gamification through the Shopee Games on user’s brand loyalty. There are two variables in this research. First, the independent variable is gamification, with dimensions of social interaction, sense of control, goals, progress tracking, rewards, and prompts. Second, the dependent variable is brand loyalty, with the dimensions of the switcher, habitual buyer, satisfied buyer, linking the brand, and committed buyer. This research is using a quantitative method. The data was collected by distributing questionnaires online to 96 respondents as a sample who were Shopee users. The result of this research indicates a moderate and positive effect between gamification through Shopee Games and brand loyalty of Shopee users.